FROM BATINBBøø TO MATLATZINCO- TOLUCA VALLEY - Albores Zárate, Beatriz (2021)
The Matlatzinco jurisdiction was located in the western part of the Basin of Mexico, whose geographic cultural landscape was characterized by the presence of the Nevado de Toluca volcano and the Lerma Lagoon, which was almost completely desiccated between 1942 and the 1970's. The Matlatzinco was invaded in 1474 by the Mexica-Tenochcas (hegemonic group in that basin), Nahuatl speakers. Matlatzinco was invaded around 1474 by the Mexica-Tenochcas (hegemonic group in that basin), speakers of Nahuatl. The names of that jurisdiction, which are known at present, are those given in Nahuatl by the Mexica invaders: Matlatzinco, and later by the Spaniards: Toluca Valley. The article proposes three Matlatzinca toponyms - the language of the rulers of this jurisdiction.